How immigrants impact their homelands - Eckstein, Susan, 1942-; Najam, Adil (Duke University Press, 2013)
This collection examines the economic, social, and cultural effects that immigrants have had on their home countries, including China, Cuba, India, Mexico, Mozambique, the Philippines, and Turkey.